Message - Abdullah, Dr. Asia Selman (Universal Journal of Pharmaceutical Research, 2017)
I am pleased to express my deepest congratulations to all staff and members of Universal Journal of Pharmaceutical Research (UJPR) for their progressive success in scientific publication pathway. The main objective of the UJPR is the continuous development to meet the highestacademic publication standards by promoting the release of scientific papers of good quality to cover a broad scope of pharmaceutical studies in different fields. Such excellent and thorough manuscript review process is encouraged to produce a UJPR of high quality and repute among other international journals. I am expecting more success for our journal to be indexed in the famous indexing such as Scopus and Thomson Reuters. Finally, enthusiastic thanks to all sincere contributors to the success of the journal to cover wide audience interests globally and to disseminate the research internationally which makes the UJPR takes part in contributing to the scientific field effectively.